KARAKTERISTIK CROSS LAMINATED BAMBOO SEBAGAI BAHAN KOMPOSIT STRUKTURAL - Ana Agustina, Naresworo Nugroho, Effendi Tri Bahtiar, Dede Hermawan (Jurnal Teknologi Industri Pertanian, 2015)
The research produced Cross laminated bamboo (CLB) to examine the effect of layer thickness andorientation angle of CLB layer on physical and mechanical properties of CLB products. In this study, thepreparation of the angular variation between CLB layer with an angle between the core and face/back of 0o, 45oand 90o were investigated. The type of bamboo used was betung bamboo splits were cut into size of 115 cm x 2cm with thickness of 0.80 cm, 1.00 cm and 1.33 cm respectively. The CLB products were made with a thicknessof 4 cm by using isocyanate adhesive (glue spread 280 g/m2). Testing was conducted on the test density, moisturecontent, swelling and shrinkage volume, delamination, bonding strength, compresive strength parallel to grain,MOE and MOR with reference to ASTM D 143 (2005), and JAS 1152 (2007). Based on the test results, the valueof delamination, MOE, MOR, and bonding strength were still under the standard requirements of JAS 1152(2007). When compared with CLT (Cross Laminated Timber) products of solid wood which had a value ofcompressive strength parallel to the fiber of 245 kg/cm2, compressive strength parallel to grain value of CLBcould reach 434 kg/cm2.Keywords: cross laminated bamboo, bamboo betung, isocyanate adhesive, physical mechanical properties